Factors associated with survival among adults with HIV-associated TB in Guangxi, China: a retrospective cohort study. (September 2012) - Zhang, Yao; Sun, Kai; Yu, Lan; Tang, Zhirong; Huang, Shaobiao; Meng, Zhihao; Zheng, Yuanjia; Wen, Yi; Zhu, Hao; Chen, Ray Y; Varma, Jay K; Zhang, Fujie
Aim: Although China has the second highest burden of TB in the world and faces a burgeoning HIV epidemic, the epidemiology and 12-month clinical outcomes of HIV-infected TB patients have not previously been reported.Methods : We reviewed records of all HIV-infected adults diagnosed with culture-confirmed TB from four HIV clinics in Guangxi, China from August 2006 to December 2008. Factors associated with patients' survival within 12 months after TB diagnosis were evaluated in Cox proportional hazards models.Results: Among the 201 patients included, 47 (23%) died within 12 months. Median CD4 count at TB diagnosis was 37 cells/mm 3 (interquartile range: 16–102). Receiving HAART (adjusted hazard ratio [AHR]: 4.2; 95% CI: 1.6–10.8), receiving TB treatment (AHR: 9.0; 95% CI: 1.5–53.5) and baseline BMI ≥ 18.5 (AHR: 8.4; 95% CI: 1.9–35.8) were independently associated with survival. Among 171 (85%) patients who received TB treatment, receiving HAART (HR: 5.1; 95% CI: 2.4–10.7) was the only factor significantly associated with survival.Conclusion: HIV-infected Chinese patients diagnosed with TB in Guangxi are at high risk of death within 12 months, a risk that is strongly mitigated by antiretroviral therapy. Improving survival from HIV-associated TB in China will require the integration of TB and HIV programs to improve access to treatment for both diseases.